Certain aspects involving anorexia nervosa in female adolescents - Soares, Lidiane Vitória Silva; Santiago Netta, Maria Denize Lelo; do Nascimento Júnior, Arthur Pereira; Barbosa, Erêndira Linhares Batista (Seven Editora, 2023)
Considering the severity of anorexia nervosa in adolescents, this study aims to understand some aspects involving this disease in female adolescence. To achieve this purpose, a literature review was carried out in the online databases: Virtual Health Library (VHL) and Scientific Electronic Library Online (SCIELO) digital library, obtaining as a final result nine studies from research with primary data, which met the objectives proposed here. Data analysis allowed presenting some causes of anorexia nervosa; Certain difficulties experienced by female adolescents with anorexia nervosa, due to this disorder; Demonstrating the relationships between adolescents diagnosed with AN and their mothers, and the challenges faced by the latter. Also, the care provided by health professionals to adolescents diagnosed with anorexia nervosa, and the difficulties they face at work. In addition to suggestions for intervention in the face of this serious public health condition. The relevance of this work is to present the context of anorexia nervosa, that is, the various aspects and implications of this disorder, which negatively affects, mainly, women in adolescence, but also their families, and poses challenges to public health, with the possibility of forming challenges to health professionals who provide services to this public. This means that the anorexia nervosa phenomenon in adolescence is also a serious social problem, which lacks discussions like the present one, to raise awareness among the population, and thus point out this problem, which is often overlooked by the competent authorities. As well as supporting actions aimed at obtaining the necessary subsidies in the fight to save the lives of people affected by this sad condition.DOI:https://doi.org/10.56238/alookdevelopv1-087